Ftalocianinas metálicas como mediadores de elétrons para determinação voltamétrica de ácido tartárico e aminas biogênicas em vinhos - Lourenço, Anabel Santos (2020)
The need to study and quantify constituents present in numerous matrices justifies the development of analytical methods and the use of chemically modified electrodes with redox mediators. The use of these sensors allows studies with species of great impact, industrial, environmental and for human health. In this context, the use of metallic phthalocyanines (MPCs), as electron mediators, has been used in electroanalysis because they have properties that facilitate the transfer of electrons. The present work proposed the development of voltammetric methods using carbon paste electrodes (CPE) modified with metallic phthalocyanines. The first study consisted of investigating the voltammetric behavior of different PCs for determining TA in wines. With this objective it was verified that only cobalt (II) phthalocyanine (CoPC) is able to electrocatalyze the oxidation of TA, a fact that is related to the presence of cobalt in this complex. In this way, CoPC - CPE was developed associated with multipath calibration for the determination of tartaric acid (TA) in wines. TA is present in wine in high concentrations, and its quantification is extremely important, considering its influence on the organoleptic properties, stability and microbiological characteristics of this drink. The presence of other organic acids in wine made it impossible to univariate the determination of TA, since these acids show a response signal in potentials very close to that of TA, thus using U-PLS/RBL modeling, a chemometric tool capable of quantifying a or more analyte in the presence of interferents. The response potential and sensitivity vary with the pH change of the medium, presenting greater sensitivity in acetate buffer (pH = 4.5) with a linear response range of 10 to 100 μmol L-1 (r = 0.9999) and LOD and LOQ of 7.29 mol L-1 and 22.1 mol L-1, respectively. Still with the study of wines, the second study proposed the simultaneous determination of biogenic amines (ABs), constituents that are also present in wines and can decrease the quality of this drink. In addition, these ABs, especially tryptamine (Trip) and histamine (Hist), have high toxicological potential for human health, even causing several symptoms of intoxication, even when present in low concentrations. Although there are no regulations that determine the quantity of these substances in wines, knowledge of the presence of these species is extremely important to assess the quality of the wine and to avoid intoxication caused by the ingestion of this drink. Thus, the CPE - NiPC was developed for simultaneous determination of Hist and Trip in wines. Studies have shown that, in addition to NiPC, other MPCs electrocatalyze the oxidation reaction of these amines, however only NiPC contributed to the high sensitivity of the proposed method. The response potential and sensitivity of the two analytes depend on the pH, obtaining optimal responses in phosphate buffer, pH = 8.5 with a linear response range of 0.49 - 3.93 ng mL-1 for Trip and 0.37 - 2.9 μg mL-1 for Hist and LOD of 0.168 ng mL-1 and 0.038 μg mL-1 and LOQ of 0.59 ng mL-1 and 0.115 μg mL-1, for Trip and Hist, respectively. The results obtained revealed the importance of using MPCs as electron mediators for the electrocatalysis of the different chemical species present in wines.